2013
DOI: 10.1111/acv.12046
|View full text |Cite
|
Sign up to set email alerts
|

Losing uniqueness – shifts in carabid species composition during dry grassland and heathland succession

Abstract: Dry sand ecosystems, such as dry grasslands and heathlands, have suffered habitat loss and degradation due to land-use changes and are today among the most endangered habitats in Central Europe. To evaluate the impact of degradation processes on habitat quality, we investigated how succession from sparse vegetated sand ecosystems to grass-invaded and tree-dominated ecosystems and the environmental parameters associated with it influences carabid assemblages. We also determined to what extent typical xerophilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
(56 reference statements)
1
11
1
Order By: Relevance
“…Omniphagous species are less sensitive to such changes. It is known that representatives of higher trophic levels (carnivorous) react to the amount of precipitation [70]. The low number of granivorous taxa in our studies is explained by the fact that they predominate in open habitats [71], and they are known to also be sensitive to moisture reduction [72].…”
Section: Discussionmentioning
confidence: 63%
“…Omniphagous species are less sensitive to such changes. It is known that representatives of higher trophic levels (carnivorous) react to the amount of precipitation [70]. The low number of granivorous taxa in our studies is explained by the fact that they predominate in open habitats [71], and they are known to also be sensitive to moisture reduction [72].…”
Section: Discussionmentioning
confidence: 63%
“…Alterations occurring in the abundance and diversity of primary consumers can flow up through the food chain to affect populations of predators and parasitoids ( Suttle et al, 2007 ; Lee et al, 2014 ), which may themselves be more sensitive to climatic change ( Voigt et al, 2003 ). Buchholz et al (2013) found reductions in semi-dry grassland spider and carabid diversity and abundance under water-limited conditions. However, at a similar site 3 years earlier, the same authors found no change in spider species richness, composition or abundance under precipitation manipulation ( Buchholz et al, 2010 ).…”
Section: Invertebrate Responses To Precipitation Changementioning
confidence: 89%
“…Arrows: indicates increases in the given metric, represents declines and denotes more varied results. References are given by the numbers on the diagram: (1) Barnett and Johnson (2013) , (2) Buchholz et al (2013) , (3) Coupe et al (2009) , (4) Davis et al (2006) , (5) Fay et al (2002) , (6) Fay et al (2003) , (7) Guo et al (2009) , (8) Heisler-White et al (2009) , (9) Kasper et al (2008) , (10) Lambeets et al (2008) , (11) Lee et al (2014) , (12) Lenhart et al (2015) , (13) Masters et al (1998) , (14) Palmer (2010) , (15) Staley et al (2007) , (16) Staley et al (2008) , (17) Suttle et al (2007) , (18) Walter et al (2012) , (19) Warne et al (2010) , (20) Zhu et al (2014) .…”
Section: Discussionmentioning
confidence: 99%
“…While many lowland heathlands have been converted to arable fields, montane heathlands have largely disappeared because of abandonment of traditional land use (Hahn, 2007; Schubert et al, 2008) and afforestation (Symes & Day, 2003; Walker et al, 2004). In general, heathlands are characterised by highly specialised and, thus, often threatened species (Buchholz et al, 2013; Schirmel & Fartmann, 2014). As a result, they are of great value for biodiversity conservation and are protected by the EU Habitats Directive (EC, 2007).…”
Section: Introductionmentioning
confidence: 99%